Mitigasi Pelanggaran Hukum Penggunaan Media Sosial Melalui Teknologi Informasi - Haspada, Deny; Mauluddin, Amras; Santana, Dimas Zulfa; Kusnaedi, Wildan (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2023)
The law also regulates daily activities via cyberspace or the internet, which has now been contained and regulated in the ITE Law (Electronic Information and Transactions Law) is a law that regulates electronic information and electronic transactions. Apart from regulating electronic transactions, the ITE Law is often used to enforce the law for violations of the law in the form of insults, defamation and unpleasant acts or bullying, hate speech, incitement and false news carried out using computers, computer networks and other electronic media. in the form of mobile phones, tablets, iPads via the internet (Social Media). To prevent or mitigate the occurrence of crime on social media, this Android-based smartphone application functions to inform users about the dangers of social media crime and how to prevent it, so an application is created which contains warnings and also additional insight for users in dealing with crime on social media. every student at Bina Mulya Mandiri Middle School, Tani Mulya Village, Ngamprah District, West Bandung Regency when turning on their cellphone. The output target to be achieved is increasing the knowledge and awareness of Bina Mulia Mandiri Middle School students and educators in utilizing Information Technology as an effort to prevent legal violations on social media.